2003
DOI: 10.1892/0891-6640(2003)017<0213:pacuos>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Clinical Utility of Sodium Bromide (NaBr) as an Estimator of Extracellular Fluid Volume in Horses

Abstract: The purpose of this study was to describe the pharmacokinetics of bromide in horses and to evaluate the corrected bromide space as an indicator of extracellular fluid volume (ECFV) in horses after the administration of a single dose of bromide by intravenous infusion. Sodium bromide (30 mg/kg of body weight, IV) was administered to 6 clinically healthy mares over a period of 3 minutes. Blood samples were collected before infusion and at intervals between 0.5 hours and 53 days after infusion. Mean elimination h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Pharmacokinetic evaluation of the intravenous administration of sodium bromide (NaBr) in horses has recently been reported. 24 horses in the current study demonstrated minor proprioceptive deficits and mild ataxia within 4 d of the administration of loading doses. Serum bromide concentrations for these two horses at these times were 1718 mg/mL and 1604 mg/mL, consistent with reports of side effects in some patients at concentrations above 1500 mg/mL.…”
Section: Discussionmentioning
confidence: 56%
“…Pharmacokinetic evaluation of the intravenous administration of sodium bromide (NaBr) in horses has recently been reported. 24 horses in the current study demonstrated minor proprioceptive deficits and mild ataxia within 4 d of the administration of loading doses. Serum bromide concentrations for these two horses at these times were 1718 mg/mL and 1604 mg/mL, consistent with reports of side effects in some patients at concentrations above 1500 mg/mL.…”
Section: Discussionmentioning
confidence: 56%
“…The previously described sodium dilution principle can be used to give an estimated range of the change in ECFV that may have occurred in these horses . Assuming an ECFV of between 80 and 120 L before treatment, horses in the HSS group would have experienced an estimated expansion of between 15.9 and 17.9 L using previous studies for approximate weights of endurance horses and approximate size of the equine ECFV . Conversely, horses in the ISS group would have an estimated expansion of only 7.5–7.7 L which is approximately the amount of fluid administered.…”
Section: Discussionmentioning
confidence: 99%
“…28 Assuming an ECFV of between 80 and 120 L before treatment, horses in the HSS group would have experienced an estimated expansion of between 15.9 and 17.9 L using previous studies for approximate weights of endurance horses and approximate size of the equine ECFV. 29,30 Conversely, horses in the ISS group would have an estimated expansion of only 7.5-7.7 L which is approximately the amount of fluid administered. A comparison anywhere in the physiologic range of ECFV would yield a highly significant difference between expansion with HSS and ISS (P < .0001).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, potassium bromide should not be the sole agent used to treat ongoing seizures. 31,32 Potassium bromide (initial dose of 25-40 mg/kg/ day PO) should be administered in combination with phenobarbital. The suggested therapeutic concentration, based on a study in dogs, is 1-3 mg/ml when used as a monotherapy and 1-2 mg/ml when used in combination with phenobarbital.…”
Section: Anticonvulsant Therapymentioning
confidence: 99%
“…13 Bromide will artificially increase the assayed concentration of serum chloride, if performed using an ion-specific electrode, and should be suspected as the cause of apparent hyperchloridaemia. 32 Although phenytoin is not routinely used as an anticonvulsant in horses, it may be considered as an alternative therapy if previous drugs are ineffective. Phenytoin appears to inactivate voltage-dependent neuronal sodium channels, to prevent depolarization of the presynaptic neuronal membrane at the excitatory nerve terminal, and thus to reduce release of glutamate, the excitatory neurotransmitter.…”
Section: Anticonvulsant Therapymentioning
confidence: 99%